2009
DOI: 10.1002/jcc.21377
|View full text |Cite
|
Sign up to set email alerts
|

A universal scale of aromaticity for π‐organic compounds

Abstract: Aromaticity is an essential concept in chemistry, invented to account for the stability, reactivity, molecular structure, and properties of many organic and inorganic compounds. In recent years, numerous methods to quantify aromaticity based on the energetic, magnetic, structural, and electronic properties of molecules have been proposed but none of them is universal. The inability of establishing a universal scale of aromaticity based on a single parameter is due to the multidimensional character of this phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 67 publications
1
36
1
Order By: Relevance
“…ASE and χ G [11] measures consider pyrrole to be more aromatic than thiophene, whereas according to NICS(1) [31] measure thiophene is more aromatic. Other versions of NICS [1,22] indicate a classification that agrees with ASE and χ G .Onthe other hand, the HOMA [11] index gives comparable values for both molecules. Figure 4(a) shows the ratio of the harmonic signal of pyrrole to furan for three different intensities at 1825 nm.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…ASE and χ G [11] measures consider pyrrole to be more aromatic than thiophene, whereas according to NICS(1) [31] measure thiophene is more aromatic. Other versions of NICS [1,22] indicate a classification that agrees with ASE and χ G .Onthe other hand, the HOMA [11] index gives comparable values for both molecules. Figure 4(a) shows the ratio of the harmonic signal of pyrrole to furan for three different intensities at 1825 nm.…”
mentioning
confidence: 74%
“…For this part, we focus our study on the five-membered ring molecules pyrrole (C 4 H 5 N), thiophene (C 4 H 4 S), and furan (C 4 H 4 O) that differ by a heteroatom. This is because (i) most measures of aromaticity are affected by the molecular size, making it difficult to compare molecules with different ring sizes [22], and (ii) the degree of aromaticity in these molecules was intensively investigated in the literature using different indicators. We show that the relative ratios of the plateau harmonics follow the same sequence proposed by most measures.…”
mentioning
confidence: 99%
“…However, occasionally, different aromaticity indices provide a concordant pattern of aromaticity [17]. Interestingly, for series of compounds, it has been shown that it is possible to derive a unified aromaticity index [18]. It is important that the π-electron structure of a substituted aromatic system is usually quite resistant to the substituent effect [19,20].…”
Section: Introductionmentioning
confidence: 98%
“…There is increasing interest in studying the structural chemistry of these compounds, and numerous papers have recently been devoted to quantifying the aromaticities and other properties of these compounds [31][32][33][34][35][36]. The reliability of geometry predictions of heptafulvene obtained through various computational methods has also been assessed [37].…”
Section: Introductionmentioning
confidence: 99%